2013
DOI: 10.1007/s00221-013-3568-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of visceral inputs on the processing of labyrinthine signals by the inferior and caudal medial vestibular nuclei: ramifications for the production of motion sickness

Abstract: Neurons located in the caudal aspect of the vestibular nucleus complex have been shown to receive visceral inputs, and project to brainstem regions that participate in generating emesis, such as nucleus tractus solitarius and the “vomiting region” in the lateral tegmental field (LTF). Consequently, it has been hypothesized that neurons in the caudal vestibular nuclei participate in triggering motion sickness, and that visceral inputs to the vestibular nucleus complex can affect motion sickness susceptibility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 63 publications
(119 reference statements)
3
17
0
Order By: Relevance
“…In particular, intragastric injection of CuSO 4 resulted in a >50% alteration in the magnitude of responses to vestibular stimulation of 28/51 (55%) parabrachial nucleus neurons (Suzuki et al 2012), 8/22 (36%) lateral tegmental field neurons (Moy et al 2012), and 16/49 (33%) neurons in the caudal aspect of the vestibular nucleus complex (Arshian et al 2013), but less than 10% fastigial nucleus neurons (p < 0.0001, χ 2 test). Furthermore, the spatial and temporal properties of responses to vestibular stimulation of the vast majority of fastigial nucleus neurons were unaffected after CuSO 4 was placed in the stomach.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, intragastric injection of CuSO 4 resulted in a >50% alteration in the magnitude of responses to vestibular stimulation of 28/51 (55%) parabrachial nucleus neurons (Suzuki et al 2012), 8/22 (36%) lateral tegmental field neurons (Moy et al 2012), and 16/49 (33%) neurons in the caudal aspect of the vestibular nucleus complex (Arshian et al 2013), but less than 10% fastigial nucleus neurons (p < 0.0001, χ 2 test). Furthermore, the spatial and temporal properties of responses to vestibular stimulation of the vast majority of fastigial nucleus neurons were unaffected after CuSO 4 was placed in the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another study indicated that the responses to vestibular stimulation of neurons in the rostral ventrolateral medulla that participate in cardiovascular regulation are exaggerated in decerebrate cats (Destefino et al 2011). Other studies compared responses to whole-body rotations of neurons in the caudal vestibular nuclei in decerebrate (Endo et al 1995; Arshian et al 2013) and conscious felines (Miller et al 2008a; McCall et al 2013) and reported little difference in findings between the preparations. Hence, it appears that decerebration is more likely to unmask responses to vestibular stimulation in brain regions that receive multisynaptic inputs from the labyrinth than areas that receive inputs directly from the inner ear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations